Превращение гусеницы - Тарасенко Лариса Тимофеевна (Познавательные сказки, 2015)
Экземпляры: Ф3 (20171006) / Инвентарный номер: 54658 / Цена: 66.00 / Сис.шифр: Д / Авт.знак: Т 19 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6